828 The Impact of a Night Float System on Neurosurgery Resident Operative Experience. (1st April 2022) - Lazaro, Tyler; Katlowitz, Kalman; Karas, Patrick Jacob; Srinivasan, Visish M.; Rao, Ganesh; Patel, Akash J.
Abstract : INTRODUCTION: Traditionally, resident call had been based on alternating call between residents in the call pool, requiring residents to work 24-hour shifts multiple times per week. However, to comply with an 80-hour work week, many programs moved toward different "float" systems, dedicating one resident to be on call for a given period of time. For surgical subspecialities, however, there has been some reticence to adopt night float due to concern for the loss of operative experience. In this study, we describe our training program's transition to the night float system and its impact on the resident operative experience. METHODS: We conducted a single program study of resident surgical case volume before and after the implementation of night float 3 of the 5 hospitals at our program over a 6-year period from 2014 to 2020. Surgical cases were obtained from the ACGME case log database. Overall surgical cases were collected from individual hospital databases. RESULTS: After the implementation of night float, there was a significant decrease in overnight call burden, specifically for senior residents who saw a decrease in call from 112 calls a year to 16. Across the three hospitals involved in the night float rotation, an average of 33 pages and 5 consults occurred each night, with a case occurring once every once every 2.75 days. Logged procedures significantly increased after the initiation of night float for participating hospitals (p<0.05, t-test), while cases at non-night float hospitals remained the same. This rise was commiserate with a global increase in hospital cases, suggesting that residents were able to take advantage of increasing opportunities. This difference was mainly driven by senior resident cases (p=0.010, t-test), as juniors and chiefs did not show significant differences in case logs (p>0.40, t-test). CONCLUSIONS: The transition to a night float call system improved our residents' operative experience by increasing their opportunities to participate in cases. In particular, senior residents had fewer night time call requirements and showed a significant increase in logged case volume.